Community participation in australian science and technology policy: the case of nanotechnology. - Harwood, Jeffrey; Schibeci, R. (Taylor and Francis Group, 2008)
Nanotechnology is widely considered to offer enormous competitive advantages to those countries that possess the knowledge and capacity to harness its potential. As in many other countries, Australia's nanotechnology policy is in its infancy and lags international research in the field. We examine the role of community engagement in the development of nanotechnology in Australia, and argue that if Australia is to establish a sustainable nanotechnology policy, then it must broaden its perspective and more carefully consider the social, ethical and environmental aspects of nanotechnology. We support the goal of shared economic growth through technological advancement; however, this seems unlikely as long as the Australian government persists with what is essentially a technical and socially exclusive approach to stimulating innovation in nanotechnology. While opposition to nanotechnology is still 'thin on the ground', it is starting to emerge and the Commonwealth and State governments would do well to treat it with respect.